Preparation and characterisation of carvacrol encapsulated in Gellan Gum Hydrogel - Hasnu Norafida, Mohd Azam Nur Aisyah Nasuha, Mohamad Jaafar Adila, (Universiti Pendidikan Sultan Idris, 2017)
Preparation and characterisation of carvacrol encapsulated in Gellan Gum Hydrogel by Hasnu Norafida, Mohd Azam Nur Aisyah Nasuha, Mohamad Jaafar Adila,